The association of nephrolithiasis with metabolic syndrome and its components: a cross-sectional analysis - Liu YT; Yang PY; Yang YW; Sun HY; Lin IC (Dove Medical Press, 2017)
Yen-Tze Liu,1 Pei-Yu Yang,2 Yu-Wen Yang,1 Hung-Yu Sun,1 I-Ching Lin1,3,4 1Department of Family Medicine, Changhua Christian Hospital, 2Department of Laboratory, Show Chwan Memorial Hospital, Changhua City, 3School of Medicine, Chung Shan Medical University, Taichung City, 4School of Medicine, Kaohsiung Medical University, Kaohsiung City, Taiwan Background: Metabolic syndrome is a worldwide disorder and also the major risk factor of several systemic diseases. Evidence identifying the association between metabolic syndrome and nephrolithiasis is lacking, especially in Taiwan.Aim: The aim of this study was to investigate the association between nephrolithiasis and metabolic syndrome and its components.Design and setting: This was a cross-sectional study conducted in the Health Examination Department of a medical center in Changhua, Taiwan, from January 2010 to December 2010.Methods: We reviewed the medical records of patients who had visited the Health Examination Center of Changhua Christian Hospital in 2010. A total of 3,886 individuals were enrolled. According to the exclusion criteria, those with an age <20 years and an abnormal renal function were excluded. A total of 3,793 subjects were included. All P-values are two tailed, and P<0.05 was defined as statistically significant.Results: The results showed a correlation between nephrolithiasis and metabolic syndrome and its components. The multivariate-adjusted odds ratio (OR) (95% confidence interval [CI]) of metabolic syndrome for nephrolithiasis was 1.318 (1.083–1.604), with a P-value of 0.006. Larger waist circumference (multivariable-adjusted OR 1.338; 95% CI 1.098–1.631; P=0.004), higher blood pressure (multivariable-adjusted OR 1.333; 95% CI 1.106–1.607; P=0.003), and increased fasting glucose (multivariable-adjusted OR 1.276; 95% CI 1.054–1.546; P=0.01) were associated with nephrolithiasis.Conclusion: This is the first study in Taiwan to investigate the relationship between metabolic syndrome and nephrolithiasis. The mechanism is controversial, and several hypotheses are offered. Adequate lifestyle modification and proper treatment in metabolic syndrome management may both contribute to nephrolithiasis prevention. Keywords: nephrolithiasis, metabolic syndrome, cross-sectional study, primary health care, preventive health services